2010
DOI: 10.1097/pec.0b013e3181fe9211
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Crisis Interventions Used in the Emergency Department

Abstract: Objective-In this systematic review we evaluated the effectiveness of emergency department (ED)-based management interventions for mental health presentations with an aim to provide recommendations for pediatric care.Methods-A search of electronic databases, references, key journals and conference proceedings was conducted and primary authors contacted. Experimental and observational studies that evaluated ED crisis care with pediatric and adult patients were included. Adult-based studies were evaluated for po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 28 publications
0
36
0
1
Order By: Relevance
“…Our previously published review identified promising evidence from three paediatric studies in favour of the use of specialised models for paediatric mental health care 10. These models were shown to reduce hospitalisation, return ED visits and length of ED stay among children with ED mental health visits; however, the findings were limited by the moderate methodological quality of the research studies and the absence of patient-reported outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previously published review identified promising evidence from three paediatric studies in favour of the use of specialised models for paediatric mental health care 10. These models were shown to reduce hospitalisation, return ED visits and length of ED stay among children with ED mental health visits; however, the findings were limited by the moderate methodological quality of the research studies and the absence of patient-reported outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A research librarian used the search strategy developed for the previous review10 to search 12 databases for literature published up to January 2015: Ovid MEDLINE (online supplementary file 1), Ovid MEDLINE In-Process and other non-indexed citations, namely Ovid Embase, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, Health Technology Assessment Database, Database of Abstracts of Reviews of Effects, ACP Journal Club, Ovid PsycINFO, CINAHL via EBSCOhost, SocIndex via EBSCOhost and ProQuest Dissertations and Theses. The previous review included literature up to March 2009; therefore, the search was restricted to the years 2008–2015.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Así mismo, los Trastornos Adaptativos, el TDAH y los Trastornos de Conducta son los tres diagnósticos más frecuentes en menores de 12 años que acuden al Servicio de Urgencias por ideación o tentativa autolítica 32 . Los niños y adolescentes con trastornos conductuales constituyen una población vulnerable con mayor riesgo de letalidad por suicidio dadas sus dificultades de adaptación social 33,34 , las elevadas tasas de ansiedad, depresión y pensamientos suicidas 35 , el mayor riesgo de consumo de drogas 36,37 y los problemas legales 38 .…”
Section: Introductionunclassified
“…In a systematic review on pediatric mental health emergency care, Hamm et al, (2010) demonstrate that specialised care management models, such as crisis intervention teams, can reduce hospitalization, A&E return visits and A&E stay. Forero et al, (2012) reviewed the existing literature on patients dying in the A&E and identified six areas where there is little research and/or suboptimal policy implementation (A&E treatment uncertainty; quality of life issues, costs, ethical and social issues, interaction between A&E and other health services, and strategies for non-hospital care).…”
mentioning
confidence: 99%